Somatic and germline mutations in the pathogenesis of pituitary adenomas. Issue 6 (December 2019) - Vandeva, Silvia; Daly, Adrian F; Petrossians, Patrick; Zacharieva, Sabina; Beckers, Albert
Abstract : Pituitary adenomas are frequently occurring neoplasms that produce clinically significant disease in 1:1000 of the general population. The pathogenesis of pituitary tumors is a matter of interest as it could help to improve diagnosis and treatment. Until recently, however, disruptions in relatively few genes were known to predispose to pituitary tumor formation. In the last decade, several more genes and pathways have been described. Germline pathogenic variants in the aryl hydrocarbon receptor-interacting protein (AIP) gene were found in familial or sporadic pituitary adenomas, usually with an aggressive clinical course. Cyclin-dependent kinase inhibitor 1B (CDKN1B) pathogenic variants lead to multiple endocrine neoplasia type 4 (MEN4) syndrome, in which pituitary adenomas can occur. Xq26.3 duplications involving the gene GPR101 cause X-linked acrogigantism. The pheochomocytoma and/or paraganglioma with pituitary adenoma association (3PAs) syndrome suggests that pathogenic variants in the genes of the succinate dehydrogenase complex or MYC-associated factor X (MAX) might be involved in pituitary tumorigenesis. New recurrent somatic alterations were also discovered in pituitary adenomas, such as, ubiquitin-specific protease 8 (USP8) and USP48 pathogenic variants in corticotropinomas. The aim of the present review is to provide an overview of the genetic pathophysiology of pituitary adenomas and their clinical relevance.